FROM TRADITION TO TRANSFORMATION: BUGIS LANGUAGE PRESERVATION IN BIAU SUBDISTRICT AMIDST INTERETHNIC MARRIAGES AND CULTURAL ASSIMILATION - Rahmatan Idul; Elmawati Jaya; Rizki Hidayah Baco (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2023)
This study explores Bugis language preservation in Biau Subdistrict, Gorontalo, Indonesia, amidst interethnic marriages and cultural assimilation. Amid Indonesia's multilingual context, local languages face marginalization due to scientific advancement and assimilation. Employing qualitative methods, the study examines language attitudes and preservation strategies of second and third-generation Bugis speakers. Second-generation speakers actively maintain Bugis through rituals and interactions, while the third-generation experiences language shift due to intermarriage. The study emphasizes targeted revitalization efforts considering intergenerational dynamics and offers insights for preserving indigenous languages. It identifies and highlights the roles of technology and government policies in addressing the Bugis community's challenges that contributes to broader discussions on language preservation